2012
DOI: 10.1523/jneurosci.0008-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Functionally Distinct Endosomal Recycling Pathways for Dopamine D2Receptor

Abstract: Dopamine D 2 receptor (DRD2) is important for normal function of the brain reward circuit. Lower DRD2 function in the brain increases the risk for substance abuse, obesity, attention deficit/hyperactivity disorder, and depression. Moreover, DRD2 is the target of most antipsychotics currently in use. It is well known that dopamine-induced DRD2 endocytosis is important for its desensitization. However, it remains controversial whether DRD2 is recycled back to the plasma membrane or targeted for degradation follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 60 publications
(64 reference statements)
2
33
0
2
Order By: Relevance
“…It has previously been suggested that constitutively internalized DAT to some extent take advantage of this fast pathway of recycling (17). Furthermore, in a recent study on the dopamine D2 receptor, it was shown that constitutive recycling of dopamine D2 receptor, and hence steady state surface levels, is sensitive to Rab4, whereas agonist-dependent recycling is sensitive to Rab11 (44). Because the transit time in rapid recycling of Rab4-positive endosomes was estimated to occur with a t1 ⁄ 2 of 1-2 min (45), a decrease in TacSERT surface expression would be expected upon treatment with the recycling blocker monensin if the steady state level of surface SERT was dependent on rapid recycling.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that constitutively internalized DAT to some extent take advantage of this fast pathway of recycling (17). Furthermore, in a recent study on the dopamine D2 receptor, it was shown that constitutive recycling of dopamine D2 receptor, and hence steady state surface levels, is sensitive to Rab4, whereas agonist-dependent recycling is sensitive to Rab11 (44). Because the transit time in rapid recycling of Rab4-positive endosomes was estimated to occur with a t1 ⁄ 2 of 1-2 min (45), a decrease in TacSERT surface expression would be expected upon treatment with the recycling blocker monensin if the steady state level of surface SERT was dependent on rapid recycling.…”
Section: Discussionmentioning
confidence: 99%
“…Our culture protocol could also be used for other types of neurons in the brain. For example, we recently used this protocol to culture striatal medium spiny neurons in a study to examine dopamine D2 receptor (DRD2) insertion in cultured mouse striatal medium spiny neurons 9 . Figure 2 shows mouse striatal medium spiny neurons cultured using our protocol at DIV 8.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The use of TIRFM to image superecliptic pHluorin-tagged receptors has been applied to several different types of neuronal receptors [7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations